(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
Metal matrix composites are getting demand now days due to their demand in different application like automobile, aircraft and marine engineering. They possess improved corrosion resistance and mechanical properties. In this work Aluminium 6061 (Al6061) alloy is used as matrix and beryl particulates are used as reinforcement. The metal matrix composites are prepared by liquid melt metallurgy technique using vortex method. Composites containing 2,4 and 6 weight percentage of beryl particulates are manufactured. Aluminium 6061 alloy was also casted in the same way for comparison.Specimensare prepared as per standard metallographic techniques. Static weight loss corrosion test of the prepared specimens is carried out in 00.025, 0.05 and 0.1 normal solutions of hydrochloric acid by immersing the specimens for a time range of 24 to 96 hours. Corrosion rates were calculated after cleaning and drying the specimen. Corrosion resistance of composites are found to be increased with increase in beryl particulate content and increase in time of exposure when compared with matrix alloy. Hence composites are more suitable than matrix alloy.